Underwater Shaking-Table Investigation of Complex Deep-Water Pile-Cap Foundation for Xihoumen Rail-cum-Road Bridge - Lei Wang; Zhong-da Lv; Fei Wang; Zhuo Zhao; Xin-long Dong (Shock and Vibration)
To study the mechanical characteristics of complex pile-cap foundations and the distribution law of hydrodynamic pressure acting on piles and cap in deep-water environments, the 60 m deep-water pile-cap foundation of Xihoumen rail-cum-road bridge was considered for this investigation. This paper focused on introducing the design and implementation process of simulating an earthquake using an underwater shaking-table test for a 1 : 60 complex pile-cap foundation model and systematically summarizing the test results. The test results showed that water reduced the acceleration of complex pile-cap foundation; however, the strain, displacement, and hydrodynamic pressure increased in varying degrees with water depths, and the maximum strain of the piles increased by 13.8% for the X-direction earthquake excitation and 15.1% for the Y-direction earthquake excitation in 1.0 m water-depth environment. The strain of the corner pile was the largest under earthquake excitation, followed by that of the front-row pile, and the strain of the middle pile was the smallest. When the water depth was 1.0 m, the maximum strain difference of each pile in the X- and Y-directions reached 26.4% and 27.5%, respectively. The hydrodynamic pressure acting on the piles decreased gradually from bottom to top, the edge pile bore more hydrodynamic pressure than the middle pile, and the hydrodynamic pressure difference between the piles reached 20%. Owing to the influence of the round-ended cap, the hydrodynamic pressure suddenly increased at the cap position, and the distribution law of the cap showed a gradually declining trend from front to side; however, the attenuation amplitude was affected by its shape.